Are chairmen and CEOS aligned in their style of disclosure? Measuring tone, complexity and forward-looking narratives and their predictability of firm future performance - Assunção, Joana Filipa Silva (2022)
This paper analyses the impact of complexity (measured by the Fog and the Flesch indexes), tone (measured by Loughran & McDonald and Henry wordlists) and forward-looking (measured by an updated version of Hussainey et al. 2003 wordlist) in firm future performance for the Chairman and CEO sections of a firm’s annual report and the alignment of these two later figures on their style of discourse. Of the five measures used, only the measure used for forward-looking narratives showed a statistically significant negative impact on future firm performance measured by the future return on assets, on the CEO section. When looking at discourse inconsistencies, results find that the CEO review portrays a higher level of complexity measured by the Fog index and holds a more forward-looking text than the Chairman section, whilst the Chairman has a higher level of complexity measured by the Flesch index and a more positive tone measured by the two different wordlists used. The results hold for financial firms, with the CEO having a more complex discourse measured by the Flesch Index for non-financial firms.